Reform and modernization of the public service in Kazakhstan and Russia (Journal of Economic Research & Business Administration, 2015)
In this article discussed such questions like modernization of the public service, conduct comparative analysis between the public service institutions in Kazakhstan and Russia.
Keywords: public service; modernization; administrative reform; anti-corruption policy; patronage system; public policy.